Knowledge, use and acceptability of menstrual cup: an explorative study among women health professionals in Kerala, India - V. M., Anjana; V. T., Jissa; G. K., Mini (International Journal Of Community Medicine And Public Health, 2024)
Background: Globally, despite a long history of invention and safety measures, the menstrual cup is not a widely used method of menstrual management among women. As comprehensive evidence on the menstrual cup use is relatively limited in India, this study aimed to describe the knowledge, use, and acceptability of menstrual cup among women health professionals in Kerala, India. Methods: We conducted a web-based cross-sectional survey among adult menstruating women health professionals. Information on knowledge of menstrual cups, pattern of use and acceptability of menstrual cups, and factors associated with the usage of menstrual cups were collected. Qualitative interviews were also conducted among current, discontinued and non-users of menstrual cup. Results: Of the 346 women studied, the majority (97%) of the participants were acquainted with menstrual cups. Ever use of a menstrual cup was reported by 34.7% of participants. Currently, women mainly used sanitary pads (73%), followed by the menstrual cup (26%) as the main menstrual hygiene product. The quantitative and qualitative analysis showed a high level of acceptability among users of menstrual cups and perceptible restraints among non-users. Environment safety and affordability were the most appealing factors for menstrual cup use. Conclusions: Nearly a fourth of health professionals in the study were currently using the menstrual cup. A high level of overall knowledge and acceptability among the users of the menstrual cup as seen in the study is likely to motivate and enhance better choice of menstrual products among women in general.